(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
Yoshihiro Francis Fukuyama, North American author, of Japanese origin, was born in Chicago in 1952. As a Political Scientist, he has a wide repertoire in the field of international politics and development, although he obtained his most important international recognition as a writer in 1992 with the publication of The End of History and the Last Man, which has been translated into 23 languages. He studied at Cornell, Yale, and Harvard Universities, and keeps in contact with the academic world teaching at Stanford University. Of neo-conservative ideas, he has had an active role in the politics of the United States during the terms of office of the last three presidents, particularly as a member of the Project for the New American Century, in support of the United States world leadership. Presently, he is acknowledged as one of the great thinkers of our days.